Factors associated with the recurrence of complicated diverticular disease - Azlanudin Azman; Ismail Sagap (Department of Surgery, UKM Medical Centre, 2011)
Colonic diverticula is observed in over 60% of the western population aged over 80 where up to 30% will eventually be symptomatic and may develop complications. The natural history and etiology of colonic diverticula have been well described. However, predictive indicators of complicated diverticular disease are not known thus preventing the prophylactic treatment of this subset of patients,. The aim of this study was to observe patients with complicated diverticular disease in order to identify common factors associated with recurrent complications. All hospital admissions from January 2005 to December 2008 for complications of diverticular disease were recruited. Using logistic regression, demographic data and factors such as clinical presentation, nature of complication, lifestyle, concomitant medical illness and medications that may be associated with recurrent episodes of complications were analyzed. A total of 121 patients were diagnosed with complicated diverticular disease during the study period with 24 patients having recurrent complications. Logistic regression analysis performed after controlling for confounders found active smoking (p=0.006) and alcohol consumption (p=0.036) along with underlying diabetes (p=0.031) and dyslipidemia (p=0.039) significantly associated with an increased risk of recurrent complications. We therefore concluded that smoking, alcohol consumption, diabetes mellitus and dyslipidemia are associated with recurrent complicated colonic diverticular disease. As these are modifiable risk factors, they should be sought for during the presentation of the first attack. Aggressive control of these factors will help in reducing the risk of recurrent complications.